2013
DOI: 10.1007/s10750-013-1445-5
|View full text |Cite
|
Sign up to set email alerts
|

Massive mortality of invasive bivalves as a potential resource subsidy for the adjacent terrestrial food web

Abstract: Large-scale mortality of invasive bivalves was observed in the River Danube basin in the autumn of 2011 due to a particularly low water discharge. The aim of this study was to quantify and compare the biomass of invasive and native bivalve die-offs amongst eight different sites and to assess the potential role of invasive bivalve die-offs as a resource subsidy for the adjacent terrestrial food web. Invasive bivalve die-offs dominated half of the study sites and their highest density and biomass were recorded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 40 publications
3
41
0
1
Order By: Relevance
“…Furthermore, drought can reduce the fluxes of terrestrial organic matter subsidies transfer to streams, thus weaken the linkage between terrestrial and aquatic ecosystems [133]. However, extreme drought may cause unexpected subsidies due to large scale mortality of invasive bivalves, and this unexpected resource subsidy may contribute remarkable amounts of nutrients and energy to the adjacent terrestrial ecosystem [134].…”
Section: Impacts Of Landscape Disturbance On Cross-ecosystem Subsidiementioning
confidence: 99%
“…Furthermore, drought can reduce the fluxes of terrestrial organic matter subsidies transfer to streams, thus weaken the linkage between terrestrial and aquatic ecosystems [133]. However, extreme drought may cause unexpected subsidies due to large scale mortality of invasive bivalves, and this unexpected resource subsidy may contribute remarkable amounts of nutrients and energy to the adjacent terrestrial ecosystem [134].…”
Section: Impacts Of Landscape Disturbance On Cross-ecosystem Subsidiementioning
confidence: 99%
“…At the same time, the establishment of the first modern, long-term academic research programs on mussel ecology by Richard J. Neves (Virginia Polytechnic and State University, USA), David L. Strayer (Cary Institute of Ecosystem Studies, USA) and Gerhard Bauer (University of Bayreuth, Germany), among others, produced numerous important publications and trained a great number of graduate students, which now lead their own research projects and provided models and support for establishment of subsequent research programs. These scientific projects soon accumulated enough critical expertise, which culminated in some modern reviews on mussel biology and ecology such as McMahon (1991), Bauer & Wächtler (2001), Strayer (2008) and Haag (2012). The American Malacological Union (now Society) had a committee on the Common and Scientific Names of Mollusks that developed a list of all mollusc species of North America, including freshwater bivalves (Turgeon et al, 1988(Turgeon et al, , 1998.…”
Section: Important Events In Freshwater Bivalve Biology and Conservatmentioning
confidence: 99%
“…One mechanism which can facilitate subsidies from aquatic to terrestrial are major floods or droughts, which can contribute to massive mortalities of freshwater bivalves (Hastie et al, 2001;Sousa et al, 2012;Bódis et al, 2014a), facilitating the accumulation of dead animals both in the aquatic and in the adjacent terrestrial ecosystems. Some studies have already showed that the biomass resulting from these die-offs may be massive (reaching dozens of kg per m 2 ; Sousa et al, 2012;Bódis et al, 2014a), with part of this carrion being consumed by higher trophic levels and the other part entering the detritus food-web (Ilarri et al, 2011;Sousa et al, 2012Sousa et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already showed that the biomass resulting from these die-offs may be massive (reaching dozens of kg per m 2 ; Sousa et al, 2012;Bódis et al, 2014a), with part of this carrion being consumed by higher trophic levels and the other part entering the detritus food-web (Ilarri et al, 2011;Sousa et al, 2012Sousa et al, , 2014. Since extreme climatic events, such as floods, droughts and heat waves are expected to occur more often in the near future in response to temperature and precipitation regime shifts (Daufresne et al, 2003;Mouthon and Daufresne, 2006;Poff and Zimmerman, 2010) the frequency of these bivalve die-offs may also increase in http://dx.doi.org/10.1016/j.limno.2014.10.002 0075-9511/© 2014 Elsevier GmbH.…”
Section: Introductionmentioning
confidence: 99%